2013
DOI: 10.1136/postgradmedj-2013-131959
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological findings of vulvovaginitis in prepubertal girls

Abstract: Positive microbiological findings, mixed bacteria cultures and a high growth of bacteria colonies are found significantly more often in girls with vulvovaginitis. The main causative premenarchal vulvovaginitis agents are faecal in origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 16 publications
(23 reference statements)
2
21
0
1
Order By: Relevance
“…Clinically, streptococcal vulvovaginitis is characterized by the signs and symptoms of acute infection: irritation, painful erythematous vulva and vagina, seropurulent and occasionally serosanguinous discharge and dysuria. 15,16 In the present study, all the girls with S. pyogenes infection had clinically manifested inflammatory reaction, and the Gram stain showed a large numbers of PMN leukocytes. In 33 examinees S. pyogenes was the only isolate, while in six examinees Staphylococcus aureus was isolated as well.…”
Section: Discussionsupporting
confidence: 54%
“…Clinically, streptococcal vulvovaginitis is characterized by the signs and symptoms of acute infection: irritation, painful erythematous vulva and vagina, seropurulent and occasionally serosanguinous discharge and dysuria. 15,16 In the present study, all the girls with S. pyogenes infection had clinically manifested inflammatory reaction, and the Gram stain showed a large numbers of PMN leukocytes. In 33 examinees S. pyogenes was the only isolate, while in six examinees Staphylococcus aureus was isolated as well.…”
Section: Discussionsupporting
confidence: 54%
“…6 In a study by Yilmaz et al, pre-pubertal children had a predominant growth of β haemolytic Streptococci. We were able to demonstrate beta haemolytic Streptococci in only two of the subjects studied which is more or less similar to the observation made by others.…”
Section: Discussionmentioning
confidence: 99%
“… Moreover, small labia minora, the absence of labial fat pads and pubic hair, poor hygiene, and risky behaviors increase the possibility that prepubertal girls will develop vaginitis. Several studies have reported that Streptococcus pyogenes and H. influenzae are the most common causes of juvenile vulvovaginitis . Although Staphylococcus spp., Streptococcus spp., Enterococcus spp., Corynebacteria spp., Enterobacteria spp., Leptothrix spp., Gardnerella vaginalis , Acinetobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…Because touching of the vulva and even the insertion of foreign bodies into the vagina may occur deliberately during childhood, it is reasonable to postulate that the upper respiratory tract could be a source of vaginal flora for prepubertal girls. Several studies have determined that S. pyogenes and H. influenzae are the most common causes of juvenile vulvovaginitis . Although S. pyogenes and H. influenza are components of the normal flora of the upper respiratory tract, these organisms are common causes of otitis media, pneumonia, rhinitis, and sinusitis in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation